Primary splenic histiocytic sarcoma complicated with prolonged idiopathic thrombocytopenia and secondary bone marrow involvement: a unique surgical case presenting with splenomegaly but non-nodular lesions - Yamada Sohsuke; Tasaki1 Takashi; Satoh Naoko; Nabeshima Atsunori; Kitada Shohei; Noguchi Hirotsugu; Yamada Kozue; Takeshita Morishige; Sasaguri Yasuyuki (BMC, 2012)
Abstract A 67-year-old Japanese female was followed up due to prolonged idiopathic thrombocytopenia with non-response to steroid therapy for 4 years, but recent progressive pancytopenia, hypo-albuminemia, and hypo-γ-globulinemia were presented. An abdominal CT scan revealed heterogeneously enhanced splenomegaly without any nodular lesions. A splenectomy was performed, and gross examination showed markedly hyperemic red pulp, weighing 760 g, accompanied by multiple foci of peripheral anemic infarction. Surprisingly, microscopic findings exhibited a diffuse proliferation of medium-sized to large tumor cells having pleomorphic nuclei, prominent nucleoli, and abundant eosinophilic cytoplasm, predominantly within the sinuses and cords of the red pulp, which occasionally displayed conspicuous hemophagocytosis and vascular permeation. In immunohistochemistry, these atypical cells were specifically positive for CD68 (KP-1), CD163, and lysozyme, which was consistent with histiocytic sarcoma (HS) of the spleen. Subsequently, section from the aspiration of bone marrow showed infiltration of the neoplastic cells associated with erythrophagocytosis 2 months after the operation, but never before it. Therefore, primary splenic HS presenting with secondary bone marrow involvement was conclusively diagnosed. Since early diagnosis and treatment are necessary for the HS patients with poor outcomes, splenic HS should be considered as a differential diagnosis in cases with chronic thrombocytopenia and splenomegaly. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1009474924812827